Gamification-Based Civic Education: Its Impact on High School Students' Civic Knowledge and Skills - Supriadi, Supriadi; Zulfaidah, Arini; Gunadi, Lie, Epifani Rachmad; Nasir, Mohammad (International Journal of Sustainable English Language, Education, and Science, 2025)
Effective civic education is essential to improve students' civic knowledge and skills, but the challenge of increasing student engagement in PPKn learning is still a significant problem. This study aims to investigate the effect of gamification in PPKn learning on improving high school students' civic knowledge and skills. This study used an experimental design with the ANCOVA approach, involving three classes in Sumenep, consisting of an experimental class (gamification) and two control groups (positive control with lectures and negative control). The results showed that the implementation of gamification resulted in a significant increase in critical thinking skills, with a value of F (2,26) = 65.14, p = 0.021, and ƞ2 = 0.95. The experimental group had a higher average score compared to both control groups. These findings suggest that gamification can be an effective strategy in improving engagement and quality of PPKn learning. The implications of this study provide insights for the practice of civic education and open up opportunities for further research with larger samples and longer durations.